The molecular determinants regulating redox signaling in diabetic endothelial cells - Srivastava, Swayam Prakash; Kopasz-Gemmen, Olivia; Thurman, Aaron; Rajendran, Barani Kumar; Selvam, M. Masilamani; Kumar, Sandeep; Srivastava, Rohit; Suresh, M. Xavier; Kumari, Reena; Goodwin, Julie E.; Inoki, Ken (Frontiers in Pharmacology, 2025)
Oxidation and reduction are vital for keeping life through several prime mechanisms, including respiration, metabolism, and other energy supplies. Mitochondria are considered the cell’s powerhouse and use nutrients to produce redox potential and generate ATP and H2O through the process of oxidative phosphorylation by operating electron transfer and proton pumping. Simultaneously, mitochondria also produce oxygen free radicals, called superoxide (O2−), non-enzymatically, which interacts with other moieties and generate reactive oxygen species (ROS), such as hydrogen peroxide (H2O2), peroxynitrite (ONOO−), and hydroxyl radical (OH−). These reactive oxygen species modify nucleic acids, proteins, and carbohydrates and ultimately cause damage to organs. The nutrient-sensing kinases, such as AMPK and mTOR, function as a key regulator of cellular ROS levels, as loss of AMPK or aberrant activation of mTOR signaling causes ROS production and compromises the cell’s oxidant status, resulting in various cellular injuries. The increased ROS not only directly damages DNA, proteins, and lipids but also alters cellular signaling pathways, such as the activation of MAPK or PI3K, the accumulation of HIF-1α in the nucleus, and NFkB-mediated transcription of pro-inflammatory cytokines. These factors cause mesenchymal activation in renal endothelial cells. Here, we discuss the biology of redox signaling that underlies the pathophysiology of diabetic renal endothelial cells.